Differences in interactions with the bone microenvironment between solid tumors and multiple myeloma: pathogenetic aspects. Possibilities and effectiveness of osteomodifying agents in multiple myeloma - A. V. Snegovoy; V. B. Larionova; I. B. Kononenko (Онкогематология, 2021)
Bone metastasis is one of the most common manifestations of advanced malignant process. Many tumors, especially breast, prostate and lung cancer, multiple myeloma, are characterized by a high incidence of bone damage (up to 7080 %) and clinical complications. Intense pain, hypercalcemia, spinal cord compression, pathological fractures, the need for radiation and surgical treatment (combined in the name «skeletal system related events») can occur even with single metastases. In the treatment of patients with bone metastases, a multidisciplinary approach is used; however, the basis is specific antitumor therapy and osteomodifying agents. They affect bone remodeling and microenvironment.